Efektivitas Metode Langsung dalam Meningkatkan Keterampilan Berbicara Bahasa Arab - Sya'bani, Muhammad Zaky (An Naba, 2021)
Arabic language which is a foreign language in Indonesia has now been studied in schools specifically based on Islamic religion. As an Arabic language subject certainly has indicators in a learning, one of them is SMP IT Al Farabi which wants to improve the ability to speak students by applying Direct Methods to learning in the classroom. Researchers collect data through observations, interviews, and documentation. The results of the data are then analyzed qualitatively. From the results of the research that has been carried out it was found that learning Arabic by applying Direct Methods can improve students' language skills especially on students' speaking skills, in addition students' interest and motivation increases. This is evidenced by the increasing value and activity of students during the Learning Process of Arabic using Direct Method.